Development of Circle Time E-Module Through Linktree to Improve Students Narrative Text Content Speaking Skills - Devi Rohmawati, Dwi Maryani; SB, Nugraheti Sismulyasih; Purwati, Panca Dewi (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop and test the feasibility, practicality, and effectiveness of the Circle Time E-module through Linktree to improve students' narrative text content speaking skills. This research used the Research and Development (R&D) method with the Borg and Gall development model. The data collection techniques used were tests (pretest and posttest questions) and non-tests (observation, interviews, documentation data, and questionnaires). The data analysis technique in this study used the normality test, t-test, and gain test. The results of the feasibility test obtained a percentage of the assessment, namely from the media expert validator of 90.8% and the material expert of 90% so that the average was 90.4% with a very feasible category. The effectiveness of the Circle Time E-module through Linktree was proven through a t-test which showed a significance value <0.05 which means there is a significant difference between speaking skills before and after treatment with an N-gain test value of 0.662 on a small scale and 0.642 on a large scale which shows a medium category. Practicality is demonstrated by the positive response of 96% of teachers and 96.5% of students with very positive criteria. From these results, it can be concluded that the Circle Time E-module through Linktree is effective, feasible, and practical for improving narrative text speaking skills in Indonesian language learning for grade IV elementary school students.